1985
DOI: 10.1007/bf00269365
|View full text |Cite
|
Sign up to set email alerts
|

Shikimate pathway activity in shake and fermenter cultures of Cinchona succirubra

Abstract: Cell suspension cultures of Cinchona succirubra were cultivated in shake cultures and for the first time in airlift fermenters. Under both conditions L-tryptophan exerts a stimulatory effect on alkaloid formation. In this context the regulatory pattern of some shikimate pathway enzymes was investigated in non-supplemented and tryptophan supplemented Cinchona cell cultures. A remarkable increase of tryptophan decarboxylase (TDC) activity was observed in Cinchona cells under the influence of tryptophan. Apparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

1987
1987
1992
1992

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 22 publications
1
4
0
2
Order By: Relevance
“…Further work has been undertaken to evaluate the effect of the time of feeding L-tryptophan on alkaloid yield. Other workers [6,[8][9][10][11] have reported L-tryptophan to have a much more pronounced effect on the growth of cell suspension cultures of Cinchona species, which in some instances has even resulted in cell death [11]. When compared with the control flasks a slight decrease in the final fresh weight was noted in the supplemented flasks, comparable to earlier findings [2].…”
Section: Feeding Experiments With L-tryptophansupporting
confidence: 84%
“…Further work has been undertaken to evaluate the effect of the time of feeding L-tryptophan on alkaloid yield. Other workers [6,[8][9][10][11] have reported L-tryptophan to have a much more pronounced effect on the growth of cell suspension cultures of Cinchona species, which in some instances has even resulted in cell death [11]. When compared with the control flasks a slight decrease in the final fresh weight was noted in the supplemented flasks, comparable to earlier findings [2].…”
Section: Feeding Experiments With L-tryptophansupporting
confidence: 84%
“…Tryptophan feeding, nevertheless, slightly enhances TDC activity; in three separate experiments, the mean TDC activity (day 0-5) in tryptophan-fed seedlings was found to be increased by 39 12% (± SD) compared with untreated control seedlings. A stimulatory influence of tryptophan feeding on TDC activity has been reported for Cinchona cell cultures too (12). However, despite the enhancement in TDC activity in tryptophan-fed seedlings, the level of tryptamine is not very much influenced (Fig.…”
Section: Alkaloid Biosynthesis In Etiolated Seedlingsmentioning
confidence: 93%
“…Interestingly, in one study, tryptophan feeding was reported to have a stimulatory influence on TDC activity (12). On the other hand, the hypothesis has been put forward that increased cellular tryptamine levels have an inhibitory effect on the expression of TDC activity in Catharanthus cell cultures (7).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…B. bakterielle Systeme, Zellkulturen von Cinchona succirubra, Ruta graveolens oder Nigella damascena rnit KiWerten um 1-5 pmol/l; SCHMAUDER et al 1985SCHMAUDER et al , 1984HERTEL et al 1988 Maximalgeschwindigkeiten der Enzyme der Alkaloidbiosynthese wesentlich hoher sirid als die Alkaloidsyntheserate in vivo (z. B. LUCKNER und Roos 1982).…”
Section: Regulatorische Eigenschaftenunclassified